2020
DOI: 10.17338/trainology.9.1_15
|View full text |Cite
|
Sign up to set email alerts
|

The effects of an 8-week off-season period on the mechanical properties of sprinting in professional rugby league players: implications for training recommendations

Abstract: To determine the change in mechanical properties of sprinting performance across an 8-week off-season period in professional rugby league players. Design: Repeated measuresMethods: Twenty-six professional rugby league players from a single rugby league team competing in Super League completed two assessments of linear sprint performance during final week of the season and second week of preseason. Linear split times were used to model the horizontal force-velocity profile and determine theoretical maximal forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
1
7
1
Order By: Relevance
“…Conversley, Jensen et al (2018) reported improvements in _ VO 2max , squat strength and vertical jump, alongside increases in body fat percentage in collegiate rugby players after a 4-week unsupervised training break. These findings are in contrast to professional adult male rugby league players (Dobbin et al 2020) and national league male adult rugby union players (Nirmalendran and Ingle 2010) who reported reductions in strength, power, speed and aerobic endurance after 8-and 6-week unsupervised off-seasons, respectively. It remains to be elucidated what effects longer periods of unsupervised training would have on the physical qualties of young rugby players.…”
Section: Introductioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Conversley, Jensen et al (2018) reported improvements in _ VO 2max , squat strength and vertical jump, alongside increases in body fat percentage in collegiate rugby players after a 4-week unsupervised training break. These findings are in contrast to professional adult male rugby league players (Dobbin et al 2020) and national league male adult rugby union players (Nirmalendran and Ingle 2010) who reported reductions in strength, power, speed and aerobic endurance after 8-and 6-week unsupervised off-seasons, respectively. It remains to be elucidated what effects longer periods of unsupervised training would have on the physical qualties of young rugby players.…”
Section: Introductioncontrasting
confidence: 81%
“…Further, studies exploring the positional variations in physical qualties to an off-season period are required in rugby union given forwards and backs have different qualities (Wood et al 2018). Dobbin et al (2020) reported a high variablity in the change in sprint mechanical properties in rugby league players, with backs reporting a larger decrease in force and power, and forwards reporting a larger decrease in velocity. Reductions in young rugby players' physical qualities towards the end of the in-season period (Dobbin et al 2019) implies the effect of baseline fitness (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical profiles provide the only reference data for academy rugby league players building upon research in senior players [ 14 , 15 , 16 ]. Jump profiles in senior NRL professional rugby league players [ 14 ] (measured using GymAware, Canberra, ACT, Australia) showed greater F V0rel (64.7 ± 16.9 vs. 31.3 ± 5.2 N·kg −1 ) and P Vmaxrel (44.7 ± 6.7 vs. 31.5 ± 9.6 W·kg −1 ) than the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…The sprint profiles of academy players presented were lower than super league professional players [ 16 ], including F H0 (761.8 ± 112.5 vs. 672.3 ± 121.2 N), F H0rel (8.8 ± 1.1 vs. 7.4 ± 1.1 N·kg −1 ), v H0 (9.1 ± 0.6 vs. 8.8 ± 0.7 m·s −1 ), P Hmax (1727 ± 277 vs. 1471 ± 246 W) and P Hmaxrel (19.8 ± 2.2 vs. 16.3 ± 9.6 W·kg −1 ). This is consistent with the mean sprint profiles in male international rugby league players [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation